FAKTOR-FAKTOR YANG MEMENGARUHI RETURN ON ASSETS PADA PERUSAHAAN SEKTOR PERBANKAN - Susanto, Richard; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence regarding the factors that influence the return on assets of companies in the banking sector. There are 19 samples selected in this study, with a total of 57 data on banking companies listed on the Indonesia Stock Exchange. This study used a research design with purposive sampling method. The Eviews 10 application is the application used to process the data in this study. The results shown in this study are third party funds, loan-to-deposit ratios, non-performing loans, and net interest margins have a positive influence on return on assets, operating expenses on operating income have a negative effect on return on assets, capital adequacy ratio and current account saving account has no positive effect on return on assets.